Cyclodextrin glycosyltransferase from Bacillus licheniformis: Optimization of production and its properties - Martins Bonilha, Paulo Roberto; Menocci, Vivian; Goulart, Antonio Jose; Teixeira de Moraes Polizeli, Maria de Lourdes; Monti, Rubens [UNESP] (Soc Brasileira Microbiologia, 2006)
Cyclodextrin glycosyltransferase (EC 2.4.1.19) is an enzyme that produces cyclodextrins from starch via an intramolecular transglycosylation reaction. An alkalophilic Bacillus strain, isolated from cassava peels, was identified as Bacillus licheniformis. CGTase production by this strain was better when potato starch was used as carbon source, followed by cassava starch and amylopectin. Glucose and amylose, on the other hand, acted as synthesis repressors. When the cultivation was supplemented with sodium ions and had the pH adjusted between 6.0 and 9.0, the microorganism maintained the growth and enzyme production capacity. This data is interesting because it contradicts the concept that alkalophilic microorganisms do not grow in this pH range. After ultrafiltration-centrifugation, one protein of 85.2 kDa with CGTase activity was isolated. This protein was identified in plates with starch and phenolphthalein. Determination of the optimum temperature showed higher activities at 25 degrees C and 55 degrees C, indicating the possible presence of more than one CGTase in the culture filtrate. Km and Vmax values were 1.77 mg/mL and 0.0263 U/mg protein, respectively, using potato starch as substrate.
Keywords: cyclodextrin glycosyltransferase; CGTase production; Bacillus licheniformis; Bacillus beta-CD